PENGGUNAAN MEDIA AUDIOVISUAL DALAM PEMBELAJARAN BAHASA ARAB UNTUK MENINGKATKAN KEMAMPUAN MENGHAFAL MUFRODAT SISWA KELAS 4 MADRASAH IBTIDAIYAH DARUL MA’ARIF 1 SERUT SENDANGSARI, PAJANGAN, BANTUL - Ahmad Sirfi Fathani; Khafifah Khafifah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2023)
In this current era, Arabic language is not something strange to learn, but that doesn’t mean Arabic language is easy to learn. There are still many students who find it difficult to learn Arabic language even though it is often used in everyday life. Not a few Arabic teachers also find it difficult to teach Arabic language material to beginner students and students who have difficulty understanding the lesson. The most basic thing in learning Arabic is mastering the mufrodat. The controlling of mufrodat is thing that is absolutely necessary for language acquisition, because with mufrodat that is arranged into a meaningful sentence can make the interlocutor can understand it. This research seeks to apply audiovisual media as a learning medium that can make it easier for teachers to convey Arabic language material, especially mufrodat and also make it easier for students to learn in. This research is descriptive qualitative research, namely research that attempts to explain the findings of field data and information, which are then described based on certain categories. The researcher uses behavioristic theory which views that learning is the result of an interaction between stimulus and response. According to this theory, what is important in learning is input in the form of stimulus and output in the form of students’ responses to the stimulus provided by the teacher. The findings obtained from this research include: 1). The learning of Arabic language mufrodat using audiovisual media and reading method is an interesting lesson. In learning Arabic language, mufrodat is presented in audiovisual form so that it is easy to understand and memorize it. This reading method is very suitable for learning Arabic language, because the main aim of this method is to improve students’ ability to read foreign languages and the most important element of this method is mufrodat. A part from that, this reading method is considered coherent in conveying the material, starting from training in reading, interpreting and making the sentences; 2) The role of audiovisual media in learning of Arabic language is: focusing students’ attention, as an additional learning resource, entertaining the students, clarifying the material and providing the real experiences for students; 3) The advantages of audiovisual media include: the learning becomes more interesting and varied, packaging the material more concisely, making it easier for the teacher to convey the material, the media is easy to carried, saved and accessed from anywhere and anytime. The disadvantages of this media are: it is difficult to apply for students who have low comprehension skills, creates a noisy classroom atmosphere, cannot be implemented outdoors and is difficult to apply when facilities and infrastructure are inadequate.